Application of low-coverage whole-genome sequencing technology in risk stratification of colorectal adenomas - Zhili, Guo; Yuyue, Xue; Fang, Yu; Dianqun, Ren; Qin, Zhang; Jie, Liu (Frontiers in Oncology, 2025)
ObjectiveThe diagnosis of precancerous lesions of colorectal cancer (CRC) presents significant challenges in clinical practice. In this study, we conducted a clinical investigation using the UCAD technique after analyzing chromosomal copy number variations (CNVs) in formalin-fixed, paraffin-embedded (FFPE) samples from various pathological stages, aiming to evaluate the value of detecting chromosomal instability (CIN) in CRC diagnosis.MethodsBased on colonoscopic pathological findings, we selected 39 FFPE specimens of tubular adenomas, 8 FFPE specimens of villous adenomas, 16 cases diagnosed as tubular-villous adenomas, and 14 cases without defined pathological subtype classification. The UCAD technique was employed to analyze these specimens, with the objective of delineating differences in chromosomal instability among the various pathological subtypes.ResultsUCAD analysis confirmed that among 39 patients diagnosed with tubular adenomas, 12 (30.76%) exhibited CIN positivity, primarily characterized by amplifications of chromosomal segments on 13q, 7, and 8, and losses on 18q and 14q. In the 8 patients diagnosed with villous adenomas, 6 (75%) were CIN-positive, displaying amplifications at 13q, 7, 8q, and 20, along with losses at 18q and 14q. Among 16 patients diagnosed with tubular-villous adenomas, 8 (50%) demonstrated CIN positivity. Additionally, 8 out of 14 cases lacking a defined pathological subtype were CIN-positive.ConclusionThe assessment of CIN correlates with both pathological subtypes and disease progression. UCAD-based detection of CIN contributes to the diagnosis of colorectal adenomas (CRA), with aberrations in chromosomes 7 and 8 potentially being closely associated with PLCRA.